Product placement as a way of promoting on an international scale based on a series of films about James Bond - Anielak, Karolina (Ekonomia Międzynarodowa, 2015)
This article presents the characteristics of product placement as global promotion. The reader may refer to the types of product placement, its regulatory framework and its short genesis and evolution. The paper presents the results of a survey conducted on a group of 123 respondents. The survey results indicate that product placement in James Bond films is noticeable by more than 90% of respondents. The respondents have positive opinions on the use of product placement to promote the products. This may encourage potential investors to make more use of film as a medium of product placement.